2014
DOI: 10.1002/ejlt.201300282
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of high 1,3‐distearoyl‐2‐oleoyl‐sn‐glycerol content stearins produced by acidolysis of high oleic sunflower oil with stearic and palmitic acids

Abstract: Nine different stearin fractions with 1,3‐distearoyl‐2‐oleoyl‐sn‐glycerol (StOSt) contents ranging from 69–84% were obtained via fractionation from fats produced by acidolysis of high oleic sunflower oil (HOSO) with various mixtures of stearic (either 95 or 98% pure) and palmitic acids (98% pure). Samples were further treated with silica to reduce the oxidised glyceride and DAG content. Isothermal crystallisation at 20°C showed a single main peak, but evidence of crystallisation during the initial DSC transien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Fractionation is the preferred technique for obtaining triacylglycerols as diacylglycerols are removed as filtrates [8,21] , which could explain the low diacylglycerol levels in PMF-C. High amounts of diacylglycerols would greatly delay the transition of symmetrical monounsaturated triacylglycerols into more stable polymorph and further give the chocolate products undesirable physical properties. [22][23][24] Rather, as Ray et al [22] reported, low diacylglycerol levels (0.7%) had less influence on the transformation from γ into β form. In this regard, PMF-C is more suitable for producing chocolate fats compared to PMF-A and PMF-B.…”
Section: Chemical Compositionsmentioning
confidence: 99%
“…Fractionation is the preferred technique for obtaining triacylglycerols as diacylglycerols are removed as filtrates [8,21] , which could explain the low diacylglycerol levels in PMF-C. High amounts of diacylglycerols would greatly delay the transition of symmetrical monounsaturated triacylglycerols into more stable polymorph and further give the chocolate products undesirable physical properties. [22][23][24] Rather, as Ray et al [22] reported, low diacylglycerol levels (0.7%) had less influence on the transformation from γ into β form. In this regard, PMF-C is more suitable for producing chocolate fats compared to PMF-A and PMF-B.…”
Section: Chemical Compositionsmentioning
confidence: 99%
“…; Ray et al . ). However, the incorporation of LC‐PUFAs to the TAG is a challenge due to the susceptibility of LC PUFA to oxidation in acidolysis reaction.…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, the use of enzyme technology is well acceptable for food application. It has been reported that SLs are synthesized by acidolysis, esterification, and interesterification reactions with the form of free fatty acids, methyl esters and TAGs (Torres et al 2002;Srivastava et al 2006;Ray et al 2014). However, the incorporation of LC-PUFAs to the TAG is a challenge due to the susceptibility of LC PUFA to oxidation in acidolysis reaction.…”
Section: Introductionmentioning
confidence: 99%
“…[ 14 ] This yielded novel fat compositions with a high Sat‐O‐Sat content (≈40%), particularly StOSt. The stearin fractions were further isolated via solvent fractionation, with final Sat‐O‐Sat levels of ≈90, [ 15 ] and compositions similar to that of shea stearin. The levels of minor components in the stearins (diacylglycerol (DAGs) and oxidized glycerides) were reduced by silica treatment to minimize their effect on crystallization and polymorphic behavior.…”
Section: Introductionmentioning
confidence: 99%